10. Cyber protection of the digital economy and Security of the banking sector - Melnyk, Leonid; Yavorska, Tetiana; Chkan, Iryna; Мельник, Леонід Васильович; Яворська, Тетяна Іванівна; Чкан, Ірина Олександрівна (OKTAN PRINT PRAHA, 2023)
Cyber protection of the economic system is becoming more relevant and problematic every year, because cyber-attacks are becoming more frequent and sophisticated, affecting both individuals and the entire international community. At the same time, the quality of attacks decreases. The government and local authorities, the defense, financial, energy sectors, and media resources are the most attacked. The proliferation of the crypto-universe has further increased the likelihood of financial sector-wide breaches. Information technology has long been at the core of the financial system and cyber security and related threats are under close, daily, non-stop surveillance by central banks. The growing trend in cybercrime has made cybersecurity a key public policy issue for regulators and supervisors. Financial institutions, namely banks, are becoming an increasingly attractive target for cybercriminals because the financial sector attracts large IT investors, allocating significant financial resources.
Keywords: Cyber protection; economic system